Annotated checklist of the Urticaceae of Timor - Silveira, Paulo C.; Conn, Barry J.; Hadiah, Julisasi Tri; Paiva, Jorge A. R.; Silva, Helena; Wilmot-Dear, Christine Melanie (Phytotaxa, 2024)
A commented checklist of the Urticaceae of Timor is presented. The list includes 25 recorded taxa, among which, six (Elatostema strigosum Hassk., Laportea bulbifera (Siebold & Zucc.) Wedd., Laportea decumana (Roxb.) Wedd., Pilea melastomoides (Poir.) Wedd., Pilea microphylla (L.) Liebm., and Pilea angulata (Blume) Blume) are, as far as we could check, recorded for the first time. Further, six taxa are uncertain or to be discarded. Overall, the list includes 10 confirmed genera (Boehmeria, Debregeasia, Dendrocnide, Elatostema, Girardinia, Laportea, Lecanthus, Pilea, Pipturus and Pouzolzia), among which the most diverse are Pouzolzia and Laportea, both with 5 taxa, and three more (Urera, Urtica and Procris) remain unconfirmed.